2021
DOI: 10.1002/aqc.3682
|View full text |Cite
|
Sign up to set email alerts
|

Spawning areas and migration patterns in the early life history of Squalius cephalus (Linnaeus, 1758): Use of otolith microchemistry for conservation and sustainable management

Abstract: In the context of the River Rhône restoration programme, the objective of this study was to assess the dispersal and population connectivity of the European chub, Squalius cephalus (Linnaeus, 1758) in a section of the natural, free‐flowing part of the lower River Rhône. The elemental water signatures for Sr:Ca and Ba:Ca were measured at seven stations within the river section, including its tributaries and backwaters, to determine whether they could be differentiated by microchemistry. From August to October t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 108 publications
0
12
0
Order By: Relevance
“…Although used for many years to assess directly larval dispersal in coastal environments (Levin, 1990;Levin et al, 1993;Zacherl et al, 2003;Becker et al, 2005Becker et al, , 2007Carson, 2010;Fodrie et al, 2011;Kroll et al, 2016;Honig et al, 2020;Bounket et al, 2021), elemental fingerprinting of biogenic carbonate structures (such as otoliths or shells) has never been applied to vent species (Mullineaux et al, 2018;Cunha et al, 2020), even though its interest for deep-sea environments has been suggested over 15 years ago (Levin, 2006). This approach relies on the record in calcified structures of the chemical composition of the water in which they have formed (Thorrold et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Although used for many years to assess directly larval dispersal in coastal environments (Levin, 1990;Levin et al, 1993;Zacherl et al, 2003;Becker et al, 2005Becker et al, , 2007Carson, 2010;Fodrie et al, 2011;Kroll et al, 2016;Honig et al, 2020;Bounket et al, 2021), elemental fingerprinting of biogenic carbonate structures (such as otoliths or shells) has never been applied to vent species (Mullineaux et al, 2018;Cunha et al, 2020), even though its interest for deep-sea environments has been suggested over 15 years ago (Levin, 2006). This approach relies on the record in calcified structures of the chemical composition of the water in which they have formed (Thorrold et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic methods also use more direct approaches, e.g., based on parentage analyses, but these are applicable only when a very significant fraction of individuals can be sampled (Gagnaire et al, 2015), which in effect happens in only very particular systems, and certainly not in the deep-sea. Surprisingly, although it has been proposed for many years as a tool to study larval dispersal (Levin, 1990;Levin et al, 1993), and has been widely used in coastal environments (Zacherl et al, 2003;Becker et al, 2005Becker et al, , 2007Carson, 2010;Fodrie et al, 2011;Kroll et al, 2016;Honig et al, 2020;Bounket et al, 2021), the alternative approach of elemental fingerprinting of biogenic carbonate structures (such as otoliths or shells) has never been used in deep-sea species (Baco et al, 2016;Cunha et al, 2020). The success of this approach relies on the record in calcified structures of the chemical composition of the water in which they have been built (e.g., Thorrold et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, although it has been proposed for many years as a tool to study larval dispersal (Levin, 1990; Levin et al, 1993), and has been widely used in coastal environments (Zacherl et al, 2003; Becker et al, 2005, 2007; Carson, 2010; Fodrie et al, 2011; Kroll et al, 2016; Honig et al, 2020; Bounket et al, 2021), the alternative approach of elemental fingerprinting of biogenic carbonate structures (such as otoliths or shells) has never been used in deep-sea species (Baco et al, 2016; Cunha et al, 2020). The success of this approach relies on the record in calcified structures of the chemical composition of the water in which they have been built ( e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inorganic microelements in otoliths mainly come from water; therefore, the composition of microelements in otoliths of fish in different habitats varies. Strontium and calcium are some of the most commomly trace metals in otolith (Wang et al, 2009;Bounket et al, 2021). According to Farrell and Campana (1996) and Walther and Thorrold (2006), Sr and Ca in otoliths in freshwater and marine fish, respectively, are mainly from water (absorbed through gills).…”
Section: Introductionmentioning
confidence: 99%